Impact of DEFB1 gene regulatory polymorphisms on hBD-1 salivary concentration. Issue 7 (July 2015) - Polesello, Vania; Zupin, Luisa; Di Lenarda, Roberto; Biasotto, Matteo; Ottaviani, Giulia; Gobbo, Margherita; Cecco, Luca; Alberi, Giulia; Pozzato, Gabriele; Crovella, Sergio; Segat, Ludovica
Highlights DEFB1 5′ untranslated region (UTR) polymorphisms were genotyped in Italian healthy subjects. The salivary concentration of human β-defensin 1 (hDB-1) was measured in Italian healthy subjects. DEFB1 genotypes were correlated with the hDB-1 salivary concentration. The −52 G/G and −44C/G genotype were associated with high protein levels. DEFB1 5′UTR genetic variants may influence the hDB-1 expression.